Beck Scales (BDI-II, BAI, BHS, BSS, and CBOCI): Clinical and Normative Samples’ Comparison and Determination of Clinically Relevant Cutoffs - Grigutytė, Neringa; Mikuličiūtė, Vita; Petraškaitė, Karolina; Kairys, Antanas (Psichologija, 2022)
This article aims to evaluate 5 Beck scales – Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), Beck Hopelessness Scale (BHS), Beck Suicidal Ideation Scale (BSS), and Clark–Beck Obsession-Compulsion Inventory (CBOCI) – comparing clinical and normative samples, and to determine clinically relevant cutoffs. The clinical sample consisted of 242 persons aged 18–74; 39 percent were men and 61 percent were women. The normative sample consisted of 1296 persons aged 18–95; 44 percent were men and 56 percent were women. In order to compare the estimates of the normative and clinical samples of the Beck scales, a paired data study sample was formed – 230 participants from the clinical and normative groups each. The clinical sample was divided into four groups according to the primary diagnoses: 107 (46.5%) patients were diagnosed with mood (affective) disorder (F30–F39), 38 (16.5%) with neurophysical stress and somatoform disorders (F40–F49), 51 (22.2%) with disorders due to the use of psychoactive substances (F10–F19), 34 (14.8%) with high risk of suicide (X60–X84; Z91.5; R45.81). 27 percent of patients had comorbid diagnoses. The results show high internal consistency of the Beck scales in all samples. The discrimination abilities of all five Beck scales are good; the cutoffs for each Beck scale in four clinical groups are estimated. Both the total clinical sample and the 4 clinical sample groups had significantly higher BDI-II, BAI, BHS, BSS, and CBOCI scores than the normative sample. In conclusion, the Beck scales alone are not sufficient for making a decision about the clinical diagnosis.
Keywords: Beck scales; anxiety; depression; suicide; hopelessness; obsession; compulsion